Manajemen Organisasi Pendidikan: Studi Kasus Tentang Organisasi Desa Pendidikan Di Fakultas Ilmu Sosial UNJ - Alya Alifah Nuraini; Fahria Izzatul Islamiya; Vevita Ravelia (Universitas Palan, 2023)
Basically, a good organization needs good management to achieve its goals. To get the best management requires people who are able to work together in teams. Therefore, the organization and management must work well together, the use of existing resources and time can be carried out more precisely and regularly in accordance with the provisions given to achieve more effective and efficient results. The purpose of this research is to find out the organizational management in the Education Village of the Faculty of Social Sciences UNJ. The research methods used are interviews and observations. This study concludes that the efforts made to manage the organization are managing, controlling, communicating and utilizing all the resources contained in an organization. The organizational management carried out by the Education Village board is by forming several divisions that function to organize and structure the organization, identify the main tasks of each division, establish rules and responsibilities, and build an organizational culture.